Eighteen original piano duets, vol. 1764 - STRAVINSKY, Igor [et.al] (G. Schirmer. Inc., 1953)
Five easy piecesnBerceusenLittle husband, little wifenRussian songnThe dollnThree easy piecesnEtudenScherzonSlavonic dancenPas RedoublenSonata